Progress of carbon sequestration in urban green space based on bibliometric analysis - Wang, Huan; Feng, Yilong; Ai, Lijiao (Frontiers in Environmental Science, 2023)
To understand the development progress and relevant frontier research of urban green space carbon sequestration, based on the core databases such as Web of Science, CiteSpace software and bibliometric analysis methods were used to analyze the research status. The results showed that the number of papers on urban green space carbon sequestration research was on the rise., China and the United States had closer cooperation from the perspective of international cooperation institutions. Peking University, the Chinese Academy of Sciences, and Auburn University made the greatest contributions to this research field. Analyzing the keywords and the literature co-citation map, it was inferred that the hot keywords of future urban green space Carbon Sequestration research include urbanization, ecosystem services, and climate change. It was found that carbon sequestration of urban green space ecosystems research primarily focuses on Urban Green Spaces(UGS’s) diversified ecological benefits through the function of carbon sequestration, and UGS carbon sequestration accounting and urban green space management. Finally, two perspectives were proposed: (1) Urban green spaces diversified ecological benefits are achieved through the function of carbon sequestration, and (2) Urban green space carbon sequestration accounting and urban green space management promotes the development of urban green space. An overview of the international progress and basic state of urban green spaces and carbon theme research is presented in this paper, Additionally, it provides valuable references for future research and helps gain a comprehensive understanding of this field of research.